2018
DOI: 10.1039/c8ra00915e
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of the ionic liquid [bmim][triflate] over a wide range of temperatures

Abstract: Picture of the ionic liquid [bmim][triflate] at the vapor/vacuum interface. The liquid density and surface tension show linear behavior in a wide temperature range. The outer interfacial space shows a zero-surface tension zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Although ρ is a bulk measurement parameter, it strongly correlates to intra and intermolecular interaction as well as packing efficiency of ILs. 50 Hence the previously measured ρ for both β and γ-ILs at 1.5015 g cm -3 and 1.4577 g cm -3 respectively, 48 was described by the authors as dependent on the structure of the cation, including ether chain length. While other studies of different N-based ether functionalised ILs correlated ρ to the electronic structure of the ionic liquid cation.…”
Section: Ionic Liquidsmentioning
confidence: 86%
“…Although ρ is a bulk measurement parameter, it strongly correlates to intra and intermolecular interaction as well as packing efficiency of ILs. 50 Hence the previously measured ρ for both β and γ-ILs at 1.5015 g cm -3 and 1.4577 g cm -3 respectively, 48 was described by the authors as dependent on the structure of the cation, including ether chain length. While other studies of different N-based ether functionalised ILs correlated ρ to the electronic structure of the ionic liquid cation.…”
Section: Ionic Liquidsmentioning
confidence: 86%
“…The liquid-vacuum interface of melted polyethylene chains was studied directly through the simulation of a thin layer of liquid in a vacuum using the molecular dynamics method. The system was expected to behave similarly to ionic liquid films with very low vapor pressure and thermal degradation at high T values [21,22]. We simulated layers at T values of 373.…”
Section: Methodsmentioning
confidence: 99%
“…We used a long cutoff radius, r c = 7.5 σ CH 3 −CH 3 , to consider all potential interactions and avoid the use of long-range corrections at the end of the simulations, or approximated corrections during the simulation, which masks the true dynamics of the system [8,14,30]. The use of a short r c with long-range corrections can lead to correct predictions of some liquid-vapor and liquidvacuum equilibrium properties, but the dynamics of the system are dependent on the r c employed [14,21]. The TraPPE potential for linear alkanes uses harmonic potentials for bond and angle bending and a cosine function on the dihedral angles [31].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we showed that triate anions accumulated in a zone before the outermost part of the interfaces of the ionic liquid [BMIM + ][Triate À ], with the outermost layer formed by the BMIM cations with alkyl chains pointing out of the interface. 47 The ionic density proles for the ionic liquid [BMIM + ][BF 4 À ] (Fig. 3) show that the component that accumulated at the liquid-vacuum interface is also the anion group.…”
Section: Density Prolesmentioning
confidence: 99%
“…In contrast, at temperatures below the thermal stability temperature P n transforms from a region of two peaks with opposite signs at the interface to a region with intermediate negative values at the limiting temperature. The two-peak zone at temperatures below the thermal limit is associated with zones of different cohesivity-an outermost, external interfacial zone (negative peak), where the bulk liquid zone strongly attracts chains of cations in ionic liquids, 56 chains in alkanes and polymers, 45 or atoms in atomic systems. 43,44 Interactions between the outermost cohesive zone and the bulk liquid create an intermediate crunched zone, which manifests as the positive peak.…”
Section: Pressure Proles and Surface Tensionmentioning
confidence: 99%